AN OVERVIEW OF DEPRESSION ON FEMALE INMATES’ IN CORRECTIONAL SETTING IN MALANG - Sinaga, Mei; Andriany, Megah; Nurrahima, Artika (Jurnal Kesehatan, 2020)
Conditions in prisons forcing the female inmates should be able to make adjustments because it will not affect the occurrence of depression. Depression in female inmates will have an impact on other aspects, namely family, child, and community as well as the presence of a negative view of yourself, others, and future can be a bad influence in a sustainable trigger the occurrence of negative behaviors such as self-mutilation and even suicide. The purpose of this study is to describe the problem of depression experienced female inmates during a period of criminal in Prison. The research method used descriptive quantitative. Data collection was done using questionnaires Beck Depression Inventory-II (BDI-II). The subject of study as much as 103 female inmates selected using purposive random sampling with the inclusion criteria of age 18 years and above, already get the verdict to undergo a criminal past and an exclusion criterion is female inmates who are in isolation, do not have a chronic illness and recidivism. The results showed that the average level of depression in female inmates category mild. Keywords: Depression, Correctional Setting; Female Inmates